2010
DOI: 10.1128/jvi.00519-10
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T Lymphocytes Established by Seasonal Human Influenza Cross-React against 2009 Pandemic H1N1 Influenza Virus

Abstract: While few children and young adults have cross-protective antibodies to the pandemic H1N1 2009 (pdmH1N1) virus, the illness remains mild. The biological reasons for these epidemiological observations are unclear. In this study, we demonstrate that the bulk memory cytotoxic T lymphocytes (CTLs) established by seasonal influenza viruses from healthy individuals who have not been exposed to pdmH1N1 can directly lyse pdmH1N1-infected target cells and produce gamma interferon (IFN-␥) and tumor necrosis factor alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
127
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(137 citation statements)
references
References 59 publications
8
127
1
1
Order By: Relevance
“…These results suggest that CD4 + T-cell epitopes are shared between the ca and WT viruses. Our data are consistent with reports by others (18)(19)(20) including Greenbaum et al that up to 41% of CD4 + T-cell epitopes are conserved between seasonal and 2009 p-H1N1 in humans and that these epitopes are mainly located in the internal protein genes.…”
Section: Elisa Antibodysupporting
confidence: 83%
See 1 more Smart Citation
“…These results suggest that CD4 + T-cell epitopes are shared between the ca and WT viruses. Our data are consistent with reports by others (18)(19)(20) including Greenbaum et al that up to 41% of CD4 + T-cell epitopes are conserved between seasonal and 2009 p-H1N1 in humans and that these epitopes are mainly located in the internal protein genes.…”
Section: Elisa Antibodysupporting
confidence: 83%
“…The transmission of the p-H1N1 virus was reduced when guinea pigs were previously infected with seasonal H1N1 or H3N2 influenza viruses (17). Recent studies examining the molecular basis for preexisting immunity to the p-H1N1 virus have demonstrated that a number of CD4 and CD8 T epitopes (18)(19)(20) are shared between the pandemic and seasonal H1N1 viruses. Studies on the effect of seasonal influenza vaccination have had discrepant results: Ferrets that were vaccinated with seasonal trivalent inactivated vaccine (s-TIV) before receipt of an adjuvanted p-H1N1 vaccine developed higher antibody titers than animals that were not primed; however, despite the difference in antibody titer, no difference in protective efficacy was observed (21).…”
mentioning
confidence: 99%
“…Therefore, an important consideration in evaluating candidate vaccines should be the degree to which they elicit crossreactive cell-mediated immunity. Although influenza-specific T cells do not provide sterilizing immunity, they protect more broadly than neutralizing antibodies against heterologous and heterosubtypic strains through viral clearance [10,11]. Broadly cross-reactive T cell epitopes are typically located in internal proteins of influenza viruses such as the nucleoprotein (NP) and matrix (M1) segments, which are more conserved than the surface hemagglutinin (HA) and NA glycoproteins [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Since human T-cells specific for seasonal IAVs also display strong cross-reactivity with IAVs of other subtypes (Jameson et al, 1999;Kreijtz et al, 2008;Lee et al, 2008) and pH1N1 2009 viruses (Richards et al, 2010;Tu et al, 2010), it can be hypothesized that individuals with a history of IAV infection were protected from pH1N1 virus infections to a certain extent. This would imply that young children that are supposedly immunologically naïve for IAV would be more at risk for developing severe disease.…”
Section: T-cells Provide Protection Against Infection With Ph1n1mentioning
confidence: 99%